PENERAPAN PSAK NO. 106 PADA PERLAKUAN AKUNTANSI MUSYARAKAH di BMT AL-IHSAN METRO LAMPUNG (Equilibrium: Jurnal Ekonomi Syariah, 2017)
This study aims to analize the accounting treatment musyarakah in BMT Al-Ihsan is in conformity PSAK 106. This is descriptive field research. The data were collected by interview and documentation. After the data were obtained, the data were then analyzed deductively.  Based on the results of the study, BMT Al-Ihsan has less adopted PSAK 106. On the measurement and presentation of accounting which was appropriate, due to the measurement of BMT Al-Ihsan only use the funds in the form of cash, but the use of funds in the form of non-cash was considered ineffective and complicated the BMT in the management so that more risk will be borne by the BMT. Furthermore, the presentation of the recording made by BMT toward active partner was not in accordance with the rules specified in PSAK. Because the active partners only administer simply recording such as recording at the time of receipt of funds, installment payment, and the amount of profit sharing.